Transforming an azaarene into the spine of fusedbicyclics via cycloaddition-induced scaffold hopping of 5-Hydroxypyrazoles - You Zhou; Shuang-Gui Lei; Baihetiguli Abudureheman; Li-Sheng Wang; Zhi-Cheng Yu; Jia-Chen Xiang; An-Xin Wu (Nature Communications)
Abstract Skeleton editing for heteroarenes, especially pyrazoles, is challenging and remains scarce because these non-strained aromatics exhibit inert reactivities, making them relatively inactive for performing a dearomatization/cleavage sequence. Here, we disclose a cycloaddition-induced scaffold hopping of 5-hydroxypyrazoles to access the pyrazolopyridopyridazin-6-one skeleton through a single-operation protocol. By converting a five-membered aza-arene into a five-unit spine of a 6/6 fused-bicyclic, this work unlocks a ring-opening reactivity of the pyrazole core that involves a formal C = N bond cleavage while retaining the highly reactive N-N bond in the resulting product. A [4 + 2] cycloaddition of a temporarily dearomatized 5-hydroxypyrrole with an in situ generated aza-1,3-diene, followed by oxidative C-N bond cleavage, constitutes the domino pathway. A library of pyrazolopyridopyridazin-6-ones, which are medicinally relevant nitrogen-atom-rich tricyclics, is obtained efficiently from readily available materials.